Vincenzo Bellini, Norma - Kimbell, David R. B. (Cambridge opera handbooks., 1998)
Norma is by common consent the finest of the ten operas composed during Vincenzo Bellini's short career, representing his genius more comprehensively than is usually the case with any single work by an operatic composer. This 1998 handbook provides the biographical and cultural context of the opera. It gives a full synopsis and an examination of the music and poetry, which is rooted in the aesthetics of early nineteenth-century Italian opera. Professor Kimbell suggests something of the impression Norma has made on our imaginations and sensibilities in the 165 years since it was first produced in Milan in December 1831. He considers the great interpretations of the eponymous leading role. His discussion also embraces Bellini's work more generally by presenting some of the critical reactions to his music.